(untitled) (Brazilian Journal of Radiation Sciences, 2022)
The accurate evaluation of fracture mechanics properties is key to the safety of operation of high responsibility structures such as nuclear reactor components. This paper evaluates the impact of mounting orientation on the test machine of clamped SE(T) (SE(T)c) specimens on its compliance. The elastic unloading compliance is a commonly used technique to measure the crack depth of specimens within fracture mechanics tests. Inaccurate measurements affect reliability of resulting measured properties. Two mounting orientations are evaluated in this paper together with two SE(T)c specimens with different width-to-thickness ratios (W/B=2 and W/B=4). Conclusions show that machine stiffness is significantly different in both orientations, and such value has the potential to affect crack depth prediction. On the other hand, the analysis scope of this work was unable to detect significant differences between both orientations, probably because loading was limited to maintain specimen integrity. Further investigation is necessary to precisely adress the impact of this effect.